The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4041/kjod.2015.45.6.308
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric predictors of treatment outcome with mandibular advancement devices in adult patients with obstructive sleep apnea: a systematic review

Abstract: ObjectiveThe efficacy of mandibular advancement devices (MADs) in the treatment of obstructive sleep apnea (OSA) ranges between 42% and 65%. However, it is still unclear which predictive factors can be used to select suitable patients for MAD treatment. This study aimed to systematically review the literature on the predictive value of cephalometric analysis for MAD treatment outcomes in adult OSA patients.MethodsThe MEDLINE, Google Scholar, Scopus, and Cochrane Library databases were searched through December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
2
28
0
2
Order By: Relevance
“…However, the exact craniofacial structures relating to response vary, due to factors such as small samples, different measurements, and variations in treatment response definitions. 18 In this study, we used a novel application of facial photographic phenotyping. We identified four Logistic regression was used to develop prediction models for treatment response by all three criteria: (1) AHI < 5 events/h plus ≥ 50% reduction, (2) AHI < 10 events/h plus ≥ 50% reduction, (3) ≥ 50% AHI reduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact craniofacial structures relating to response vary, due to factors such as small samples, different measurements, and variations in treatment response definitions. 18 In this study, we used a novel application of facial photographic phenotyping. We identified four Logistic regression was used to develop prediction models for treatment response by all three criteria: (1) AHI < 5 events/h plus ≥ 50% reduction, (2) AHI < 10 events/h plus ≥ 50% reduction, (3) ≥ 50% AHI reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral cephalometry can identify craniofacial characteristics that could have an effect on treatment response, although no definitive clinical recommendations are available because of inherent methodological weaknesses of the currently available studies. 38 Reported improvements in subjective daytime sleepiness and health perceptions were found in both treatment groups, underscoring the therapeutic benefit of CPAP and MAD therapy at all timepoints during the follow-up period, even in patients with severe OSA. Similar findings in different studies using the same questionnaires (pooled) were reported in a review article by Chan and asociates.…”
Section: Discussionmentioning
confidence: 72%
“…Classically, shorter soft palate length, larger retropalatal airway space, lower hyoid bone position, and a smaller mandible are associated with favorable MAD treatment response. 1,65 Two recent systematic reviews, 70,71 however, exploring cephalometric predictors for MAD response found a majority of observational studies on cephalometric predictors had flawed designs and failed to control for known confounding factors such as age, gender, body mass index, and baseline AHI. Definitions of treatment success were inconsistent, and heterogeneity in design prevented data synthesis and meta-analysis.…”
Section: Cephalometrymentioning
confidence: 99%